A systematic approach to cross-cultural adaptation of survey tools. - Costa FA; Duggan C; Bates I (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Background: Involving patients in health care is increasingly acknowledged as the best way to empower patients to manage their illness. Whilst the involvement of patients is laudable and widely recognised, how much they want to be involved needs to be ascertained. Research has shown that inappropriate provision of information to patients can increase their anxieties towards illness and alter perceptions of medicines' usefulness, consequently impacting on medicines' taking behaviour. Tools have been validated in the UK to identify information desires, perceived usefulness of medicines and anxiety felt about illness. There is a need to adapt validated tools for use in other settings and countries. This paper is the first of a series describing the processes involved in the adaptation and validation of these. Aim: to review and adapt the processes established to translate and back translate scales and tools in practice. Methods: The survey tool was translated and back-translated according to published guidelines, subsequently tested in a sample of medical patients and further refined by seeking health care professionals' perceptions and input from lay people. Results: Data demonstrates the importance of including various perspectives in this process, through which sequential modifications were made to the original scales. Issues relating to religious beliefs, educational and health literacy differences between countries highlight the relevance of taking cultural values into account. Some led to significant modifications, discussed in this first paper, and tested for validity and reliability in a second paper.